CRUZIA TENTACULATA (RUDOLPHI, 1819) TRAVASSOS, 1917 IN DIDELPHIS PERNIGRA (ALLEN, 1900) IN THE ACERO MARKAVALLEY OF THE YUNGAS OF LA PAZ, BOLIVIA - Mollericona, José Luis (2014)
We report the finding of the nematode, Cruzia tentacula (Rudolphi, 1819) in the cecum of an Andean white-eared opossum Didelphis pernigra Allen, 1900 in the Yungas of La Paz, Bolivia. Sixty nematodes were cleared with lacto phenol Amman and identified as C. tentacula. This is the first record of this species in Bolivian didelphid hosts.